Ecology of Floristic Quality Assessment: testing for correlations between coefficients of conservatism, species traits and mycorrhizal responsiveness. Issue 1 (21st December 2017) - Bauer, Jonathan T; Koziol, Liz; Bever, James D
Abstract : Coefficients of conservatism (C values) are numeric values assigned to plant species to indicate their sensitivity to anthropogenic disturbance, and these values are increasingly used to prioritize natural areas for conservation and monitor restoration outcomes. However, assigning these values is subjective, and quantitative links between C values and a plant species' ecology are needed. We grew seedlings of 54 plant species in a greenhouse and measured traits that are related to life history trade-offs. We found that these traits were correlated with C values, indicating that coefficients of conservatism are closely linked to a plant species' life history strategy. Abstract: Many plant species are limited to habitats relatively unaffected by anthropogenic disturbance, so protecting these undisturbed habitats is essential for plant conservation. Coefficients of conservatism (C values) were developed as indicators of a species' sensitivity to anthropogenic disturbance, and these values are used in Floristic Quality Assessment as a means of assessing natural areas and ecological restoration. However, assigning of these values is subjective and improved quantitative validation of C values is needed. We tested whether there are consistent differences in life histories between species with high and low C values. To do this, we grew 54 species of tallgrass prairie plants in a greenhouse and measured traits that are associated with trade-offs on the fast-slow continuum of life-history strategies. We also grew plants with and without mycorrhizal fungi as a test of these species' reliance on this mutualism. We compared these traits and mycorrhizal responsiveness to C values. We found that six of the nine traits we measured were correlated with C values, and together, traits predicted up to 50 % of the variation in C values. Traits including fast growth rates and greater investment in reproduction were associated with lower C values, and slow growth rates, long-lived leaves and high root:shoot ratios were associated with higher C values. Additionally, plants with high C values and a slow life history were more responsive to mutualisms with mycorrhizal fungi. Overall, our results connect C values with life-history trade-offs, indicating that high C value species tend to share a suite of traits associated with a slow life history.